Pengenalan Tari Pendet dalam Pertukaran Budaya Markandeya-Walailak sebagai Media Pendidikan Karakter Lintas Budaya - Ni Putu Oktha Wahyunia Merta; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to discuss the introduction of the Pendet Dance in the Markandeya–Walailak cultural exchange program and to evaluate its effectiveness as a cross-cultural character education tool. To investigate program design, execution, and results, the study used a descriptive qualitative approach backed by the CIPP (Context, Input, Process, Product) evaluation model. During the cultural exchange activities, information was gathered through participant reflection, documentation, and observation. The results show that the program effectively combined the principles of character education with conventional performing arts. Thai students showed greater appreciation, tolerance, respect, and empathy for cultural diversity as well as a deeper comprehension of the Pendet Dance's meaning, symbolism, and cultural value. In addition, Indonesian students who served as facilitators saw improvements in their discipline, self-assurance, cultural adaptability, and communication abilities. The exercise emphasizes how traditional performing arts can be a powerful tool for international engagement and cultural diplomacy. All things considered, the program shows that cultural exchange programs can make a significant contribution to global character education, and it is advised that comparable projects be maintained and developed in subsequent international education partnerships.